Exploring The Role of The Entrepreneurial Ecosystem in Fostering Innovation in Youth Entrepreneurship in South Africa: A Literature Review - Chasaya, Wimbayi; Ayandibu, Ayansola (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Heightened by the Fourth Industrial Revolution (4IR), innovation was increasingly becoming significant in entrepreneurship. Moreover, according to Schumpeterian entrepreneurship, innovation was equivalent to a profit. Thus, it was imperative to investigate the extent to which entrepreneurial ecosystems promoted innovation in youth entrepreneurship.Purpose: This study investigates the role of entrepreneurial ecosystems in promoting innovation in youth entrepreneurship in South Africa.Design/methodology/approach: A literature review study based on a collection of relevant literature from online databases was conducted. Literature from 2015 to 2025 was considered to analyze and synthesize the literature on youth entrepreneurship and the entrepreneurial ecosystem.Findings/Result: Findings from the review of literature indicate that inadequate infrastructure development and funding, gaps in policy implementation and entrepreneurship education hinder innovation in youth entrepreneurship.Conclusion: This study recommends creative entrepreneurship education, a National Youth Innovation Fund, local innovation hubs, and local government intervention to enhance innovation in youth entrepreneurship in South Africa. Drawing from the Triple Helix model, the government, industry, and universities should collaborate to fund innovative business ventures, mentor creative youth entrepreneurs, and offer innovative entrepreneurship education. This study recommends empirical research on the South African entrepreneurial ecosystem, focusing on rural and township areas.Originality/value (State of the art): This article synthesizes the literature on youth entrepreneurship and innovation to inform diverse stakeholders of the current state of knowledge, key trends, research gaps, and directions for future research. Keywords: youth entrepreneurship, innovation, entrepreneurial ecosystem, innovative entrepreneurship, youth empowerment